Answer:
I believe it's the 1st one.
HOPE IT HELPS! BE SAFE :3
Answer:
x=6
Step-by-step explanation:
log(5x+10)-log(4x+12)=1-2log(3)
log(5x+10/4x+12)=1-2log(3)
log(5x+10/4x+12)=log(10)+log(3^-2)
log(5x+10/4x+12)=log(10×3^-2)
log(5x+10/4x+12)=log(10×1/9)
log(5x+10/4x+12)=log(10/9)
5x+10/4x+12=10/9
9(5x+10)=(4x+12)10
45x+90=40x+120
5x=30
x=6
if you like my answer. Please mark me as brainliest
Answer:
The origin.
Step-by-step explanation:
0 belongs in none of these quadrants but in the origin. The origin is the center dot in the middle of all quadrants.
Answer:
a
.Step-by-step explanation:
2(a+3) + 3(2a-1)
First, let's use the distributive property to expand 2(a+3):
2(a+3) = 2*a + 2*3 = 2a + 6
Let's use the distributive property now to expand 3(2a-1):
3(2a - 1) = 3*2a - 3*1 = 6a - 3
So 2(a+3) + 3(2a-1) = 2a + 6 + 6a - 3
Now you calculate variables between each others, and numbers between each others:
2a + 6 + 6a - 3 = 2a + 6a + 6 - 3 = 8a + 3
So the simplified form of 2(a+3) + 3(2a-1) is 8a + 3.
Hope this Helps! :)